Higher expression levels of aquaporin (AQP)1 and AQP5 in the lungs of arid‐desert living Lepus yarkandensis. Issue 4 (11th December 2019) - Zhang, Jianping; Li, Shuwei; Liu, Jie; Li, Lexing; Deng, Fang; Baikeli, Buheliqihan; Li, Linrui; Ma, Xuanye; Liu, Guoquan
Abstract: Water transport across epithelial cells that line the airways and alveoli is a crucial component of lung physiology. Aquaporins (AQPs) facilitate water transport across the air space–capillary barrier in the distal lung. However, the roles of lung AQPs in desert animal adaptation to dry airstream environments are still unclear. A hare ( Lepus yarkandensis ) only lives in the Tarim Basin, and its living environment is an arid climate with rare precipitation. We studied cellular localization and expression levels of AQP1, AQP3, AQP4 and AQP5 in L. yarkandensis lungs by immunohistochemistry, quantitative real‐time polymerase chain reaction and Western blot. The lung of rabbits ( Oryctolagus cuniculus ) that inhabit in mesic environment was similarly studied. Obtained results in two species of animals were compared to investigate whether AQPs in the lung altered expression in the animal living in arid region. AQP1 was localized to the endothelial cells in capillaries and venules surrounding terminal bronchioles and alveoli. AQP5 was localized to the ciliated columnar cells in terminal bronchioles and the alveolar type I cells in the alveolus. Quantitative real‐time PCR analysis showed higher AQP1 and AQP5 mRNA levels in L. yarkandensis compared to O. cuniculus . Similar results were obtained by Western blot. These results revealed that the higher expression levels of AQP1 and AQP5 played a significant role in water transport in the lungs of arid‐desert living L. yarkandensis and might accelerate water transport from capillary compartments to the airspace.